Strategies for Optimizing Health Workers’ Communication to Improve the Quality of Informed Consent among Patients from Seven Tribes (A Case Study at Mitra Masyarakat Hospital, Timika, Central Papua) - Ratna Indriana Donggori; Bayu Wahyudi; Yen Efawati (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
This study aimed to analyze the effect of healthcare workers' communication strategies on improving the quality of informed consent among patients from seven indigenous tribes at Mitra Masyarakat Hospital, Timika, Central Papua. Cultural diversity, language differences, and communal decision-making practices create communication challenges that may reduce patients' understanding of medical information. A mixed-methods approach with an explanatory sequential design was employed. Quantitative data were collected through questionnaires from patients and analyzed using multiple linear regression, while qualitative data were obtained through in-depth interviews with healthcare workers to explain the quantitative findings. The study examined effective healthcare communication, intercultural communication training and medical interpreter support, integrated communication strategies through electronic medical records, and the quality of informed consent. The findings indicate that all independent variables positively and significantly influenced the quality of informed consent, with integrated communication through electronic medical records demonstrating the strongest effect. Qualitative findings revealed that language barriers, cultural diversity, and limited health literacy remained the main challenges in implementing informed consent. These findings imply that improving informed consent quality requires strengthening healthcare workers' communication competence, expanding intercultural communication training, providing interpreter support, and optimizing electronic medical record systems to support patient-centered healthcare in multicultural settings.